1985
DOI: 10.1148/radiology.155.1.3883414
|View full text |Cite
|
Sign up to set email alerts
|

Videodensitometric ejection fractions from intravenous digital subtraction left ventriculograms: correlation with conventional direct contrast and radionuclide ventriculography.

Abstract: Forty-three patients who had undergone direct-contrast ventriculography were submitted to intravenous digital subtraction ventriculography and first-pass radionuclide ventriculography to compare the left ventricular ejection fractions obtained by each method. Ejection fractions were calculated by the area-length method from the direct contrast ventriculograms, by both area-length and videodensitometric methods from the digital subtraction ventriculograms, and by count densitometry from the radionuclide ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This comparison demonstrated that the dual-energy images were of sufficient quality to support quantitative analysis techniques. Two important quantitative techniques are densitometric analysis [7][8][9] and parametric imaging [17]. Both of these methodologies require some means of subtracting image structures unrelated to the signal of interest.…”
Section: Misregistration Artifactsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comparison demonstrated that the dual-energy images were of sufficient quality to support quantitative analysis techniques. Two important quantitative techniques are densitometric analysis [7][8][9] and parametric imaging [17]. Both of these methodologies require some means of subtracting image structures unrelated to the signal of interest.…”
Section: Misregistration Artifactsmentioning
confidence: 99%
“…Contrast enhancement allows ventriculography to be performed with direct left ventricular injection of small amounts of contrast material [1][2][3] or with a venous injection [3][4][5][6]. Subtraction allows the determination of ejection fractions from high resolution images using an intravenous injection and videodensitometric techniques [7][8][9]. The potential for measuring absolute left ventricular volume exists [10].…”
Section: Introductionmentioning
confidence: 99%
“…(2) as (6) Because this expression is already a ratio of differences, slow background changes are less important.…”
Section: Methodsmentioning
confidence: 99%
“…(5) and (6) can be small, so that the results fluctuate from beat to beat. Some of these fluctuations may 115 be due to incomplete contrast mixing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation